Adsorptive desulfurization of benzothiophene from simulated fuel using Ni/ Γ-Al₂O₃ as an adsorbent; performance, adsorption, and kinetic study - Yaqoob, Nawar; Naife, Tariq M.; Shareef, Zaid Nidhal (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Adsorptive desulfurization is essential for supplying clean fuel, reducing environmental pollution, and obtaining strict regulatory standards. This study focused on the adsorptive desulfurization of benzothiophene from simulated fuel using Ni/ γ-Al₂O₃ as an adsorbent. The study investigated the effect of nickel ions loading percentage on the removal efficiency. Also, the most fitted kinetic and isotherm models for the process were indicated. The modified adsorbent was characterized by different techniques, including XRD, FESEM, and EDS. The measurements revealed a successful modification of Ni/ γ-Al₂O₃, achieving the required loading percentages (2-10%). The desulfurization investigation was carried out under varying conditions of adsorbent dose (0.2-1 g), Ni loading percentage (2-10%), initial sulfur level of 100-260 ppm, and contact time (15-600 min). The results showed that Ultra-deep desulfurization was accomplished, with 96% sulfur removed from the initial concentration of 100 ppm at 1 g of adsorbent under room temperature and atmospheric pressure, 10% Ni ions content, and 600 min of contact time, and the highest adsorption capacity was 57.2 mg S/ g adsorbent at 260 ppm. The Langmuir isotherm model best described the process with R² of 99.9%, while the pseudo-second-order kinetic model had R² of 99.99%.